Advantages and Disadvantages of Telecommuting: An Observation - Parajuli, Dilip (Pravaha, 2020)
This paper aims to explore the advantages and disadvantages of telecommuting. In particular, the research design for the study is descriptive. A basic research tool used to gather data on the advantages and disadvantages of telecommuting is the questionnaire survey. The questionnaire was sent to 73 faculties of the three constituent campuses of Tribhuvan University. Based on the results, it is found that flexible working hours are the key advantage of telecommuting in the teaching field. The second key advantage is an improvement in time management. The third advantage is savings in travel time and expenses. The least advantage of telecommuting is professional flexibility. It is also found that feeling of isolation is one of the key disadvantages of telecommuting. The second key disadvantage is no separation between spheres of work and home that is followed by over-availability syndrome, ditched society, investment in training, and personality unsuitability. The least disadvantage of telecommuting is the lack of professional support. By avoiding such types of disadvantages, our organizations can get many benefits by adapting telecommuting as the few and flexible work methods.